Exploring Filipino consumer perspectives: identifying knowledge gaps in understanding, attitudes, and perceptions of processed foods. - Dimasin, Renee Maxine C.; Basinang, Airesse Rae P. (Quezon City University of the Philippines Diliman, 2025)
Consumer misconceptions surrounding processed foods persist, often fueled by associations with artificial additives, poor nutritional value, and chronic disease risks. This study examined Filipino consumers’ knowledge, attitudes, and perceptions (KAP) of processed foods and the factors influencing them, using a validated online survey (n = 425) that assessed demographics, food processing knowledge, attitudes on perceived healthiness, and affective perceptions of industrial processing. Knowledge scores varied significantly (p < 0.05) by age, education, sex, and primary information source. Younger respondents (18-24) and those with higher education demonstrated greater accuracy in identifying food processing levels, though misconceptions persisted across all groups. Respondents favored minimally processed foods (MPF) the most, showed moderate acceptance of processed foods (PF), and expressed the least favorability toward ultra-processed foods (UPF). Perceptions were significantly (p < 0.05) influenced by information sources, with print and TV news audiences exhibiting more negative views than those informed via online or government channels. Categorical Principal Component Analysis identified two components: one reflecting familiarity and acceptance of commonly consumed processed foods, and another indicating skepticism toward industrially processed products. These components were significantly associated (p < 0.05) with knowledge scores and attitudes, suggesting that both familiarity and perceived risk influence consumer perceptions of food processing. This study highlights the need for better public education and clearer communication about food processing. Bridging consumer knowledge gaps can help reduce stigma and support informed food choices. The findings can be beneficial in food policy, labeling, and nutrition communication to encourage evidence-based understanding of processed foods.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Food industry and trade; Processed foods -- Philippines; Consumers -- Philippines; Food consumption -- Philippines; Consumer attitude; NOVA classification; Food processing; Consumer perception; FoodProK; Filipino consumers